Investigating Islamic Meanings in the Poetry of Jareer - Khalifa Abbas, Jinan (Al-Adab Journal, 2021)
The current study aims at investigating the utilization of Quranic expressions and processing them according to poetic purpose. It adopted the analytical –descriptive methodology to discover utilizing some samples from the Glorious Quran in poetry and investigating its efficiency on poetic purposes and its reflections on society. The study views literary works in Islamic and Quranic perspectives. The study tries to discover the effect of Quran on the poet trough the variety of the included discourse. The verses of Jareer were including Islamic vocabulary according to the taste of the poet.The current study directs the attention towards the effect of Quran on the poet and the relation between the innovative level and the potential level.